Apoptosis in ischemic heart disease - Teringova, Elena; Tousek, Petr (Journal of translational medicine, 2017)
Apoptosis plays an important role in the myocardial loss after acute myocardial infarction and participates in the process of subsequent left ventricular remodeling and development of symptomatic heart failure. Finding a sensitive apoptotic marker that would help in prognostic stratification of patients after acute myocardial infarction and offer new therapeutic strategies is thus of a great importance. Several studies suggest that tumor necrosis factor-related apoptosis inducing ligand (TRAIL) represents a very promising marker of prognosis in patients with acute myocardial infarction. This review article provides an overview of current knowledge on the role of apoptosis in ischemic heart disease and highlights potentially beneficial apoptotic markers in clinical practice.
Keywords: Ischemic heart disease; receptory domény smrti; Heart failure; signální transdukce; Models, Biological; biologické modely; lidé; Signal Transduction; Outcome; Biomarkers; biologické markery; apoptóza; Apoptosis; Myocardial Ischemia; Receptors, Death Domain; Humans; ischemická choroba srdeční